Utilizações de informações genômicas para o melhoramento genético de características de crescimento em bovinos da raça Nelore - Terakado, Ana Paula Nascimento [UNESP] (2015)
Growth traits are fundamental to the genetic improvement of beef cattle, because they are directly related to the economy of the system. Recent technological advances have enabled the use of genomic data in the assessment of animals. The objective of this study was to evaluate models to predict breeding values from genomic data, and detection of DNA polymorphisms associated with growth traits in Nellore animals. Thus, it was genotyped 5,064 animals, using high-density SNPs Illumina Bovine HD assay (Illumina, San Diego, CA, USA), and after quality control 412,993 SNPs were used. In Chapter 2, three models were used to estimate the effects of markers for birth weight (BW), weight gains from birth to weaning (WGBW) and from weaning to yearling (WGWY), yearling height (YH) and cow weight (CW): better linear estimator not biased (GBLUP), BAYESCπ and Improved Bayesian least absolut shrinkage and selection operator (IBLASSO). Breeding values were desregressed and used as pseudo-phenotypes. Bayesian methods were the most suitable for estimating the effects of SNPs and genomic values for the studied traits. In Chapter 3, we applied the ssGBLUP model to estimate the effects of markers and associate them with BW, WGBW, WGWY, YH and CW. There were associations with BW in BTA (Bos taurus chromosomes) 14, with WGBW in BTA 5 and 29, with WGWY in BTA 11 and YH in BTA 8, distinguishing the genes TMEM68 (transmembrane protein 8B) associated with BW and YH, XKR4(XK, Kell blood group complex subunit-related family, member 4) associated with BW and NPR2 (natriuretic peptide receptor B) associated with the YH